PENGARUH GARAM TERHADAP PARAMETER VAN’T HOFF PADA PERSAMAAN KENAIKAN TITIK DIDIH - Setiyadi Setiyadi (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
In the equation to determine the boiling point rise , Van't Hoff  parameter is used. However  the parameters can only be used for dilute solutions. For this reason, it is necessary to do experiment to determine but for concentrated dilution. A mathematical : k = a.exp (b.m) is used to find the parameter. One hundred mililiter distilled water is added into beaker, then NaCl is also added to form NaCl solution of 0,25 molal. was added to water to form a 0.25 molal Na Solution is heated until boil and the boiling temperature n recorded. The experiment are conducted for different molality and type pf salt. The experimen shows that boiling point are  influenced by strong/weak acid and strong/weak base. Each type of salt produce parameter different. The value of constante a is 0,853 to 3,707 and constante b is -0.16 to -0.42 with  errata average above 10%.